Capacity for wonder among medical students: Assessment and educational implications. (2nd January 2023) - Geller, Gail; Shin, Seonho; Goldberg, Harry; Merritt, Maria W.
Abstract: Objective: The capacity for wonder (CfW) is a personal disposition related to lifelong learning and moral character development, two highly valued characteristics of health professionals. We previously developed and validated a CfW measure among college students. Here we describe how the scale performs among medical students. Methods: We invited all students at a top-tier U.S. medical school ( N = 477) to participate in an online survey including the CfW measure, year in medical school, and demographics. We performed confirmatory factor analysis on the CfW measure and reassessed its reliability. Results: 276 students completed the survey for an overall response rate of 58%. Factor analysis resulted in a 10-item scale with an alpha of 0.79 and an eigen value of 3.57. Factor loadings ranged from 0.43 to 0.77. The mean total score was 39.3 (SD = 8.9) out of a possible high score of 60. Total scores varied by year in school with significantly lower scores among 2nd year students (32.9 vs. 41.5; p < 0.001). Conclusion: We confirmed the reliability of a 10-item CfW scale in 4 cohorts of medical students. Results suggest that the 2nd year of medical school poses the greatest risk to students' capacity for wonder. Efforts should be made to understand this phenomenon and develop interventions to mitigate it. Future research should explore the validity of the CfW scale, its utility in evaluating interventions designed to cultivate the capacity for wonder, its applicability to other groups of health professionals, and its association with ethical decision-making and practice.